PHYTOCHEMICAL ANALYSIS, HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY, AND EX VIVO ANTIOXIDANT POTENTIAL OF A HERBAL FRUIT EXTRACT - SHARMA, GEETIKA; MISHRA, TULIKA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present investigation was to determine the presence of various phytochemicals in an ethanolic herbal fruit extract (HFE) made up by a blend of fruits of Phyllanthus emblica (PE), Ananas comosus (AC), Punica granatum (PG), and Terminalia chebula (TC). Followed by a qualitative high-performance liquid chromatography (HPLC) analysis for standardization of the extract using ascorbic acid and gallic acid as standards, this study was also aimed at the determination of ex vivo antioxidant potential and calculation of inhibitory concentration (IC50) value of HFE. Methods: The analysis of phytochemicals present in HFE was done qualitatively by methods as described by various researchers. Reversed-phase HPLC was carried out on a C-18 column on gradient mode, using methanol and acetic acid as mobile phase. Ex vivo antioxidant potential was evaluated by inhibition of lipid peroxidation (LPO) method by the preparation of packed cell volume. Results: The results revealed the presence of multiple phytoconstituents in the HFE, and through the chromatographic analysis, the presence of gallic and ascorbic acid as marker compounds was achieved. IC50 values calculated after LPO inhibition method was found to be 21.87 μg/ml and 25.63 μg/ml for ascorbic acid (as standard) and ethanolic HFE, respectively. Conclusion: The use of herbal antioxidants can provide protection to the human body by fighting against multiple diseases caused as a result of the accumulation of free radicals, generated in the normal metabolic processes going on inside the body. Nowadays, researchers are amused to see the long-term positive effects of using a combination of antioxidants, for example, a polyherbal formulation, rather than single entities.